(untitled) (Medico Legal Update, 2019)
Present retrospective study is undertaken to observe the pattern of firearm injuries in relation with the wound characteristics, manner of death and type of firearms with their range of infliction. The study sample included seventy firearm fatalities presented to the Department of Forensic Medicine and Toxicology of Government Medical College, Jagdalpur during January 2013 to December 2017. The autopsy reports were analyzed using descriptive statistics. Maximum affected male individuals were belonged to the age group of 21-30 years. The most common site for the infliction of gunshot injury was found to be the thorax followed by the upper and lower extremities. Rifled firearm weapon was used with the distant range of fire in majority of the cases. Considering the number of injuries and their location, we interpreted the homicidal nature of death in 94.29% of all cases (n = 66).